Two types of coronaelektrets discharge characteristics - Kuzmin, R.N.; Mokrynskaya, E.V. (Functional Materials, 2005)
Photodischarge characteristics of coronaelectrets were investigated. It proposed a simple model of photocondactive coronaelectrets relaxation. This model is based on the assumption of internal opposite-EMF formation. The expression for geometrical parameter of opposite-EMF was obtained. On the base of obtained experimental data, the electrical field strength and thickness dependencies of free charge carriers lifetime was calculated. It was corroborated that in riched on structural defects anthracene crystals the transport of holes attributed by their moving along nonbasic edge dislocations.